2015
DOI: 10.9721/kjfst.2015.47.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Antioxidant Activity of Sulgidduk Prepared by Addition of Aronia Powder (Aronia melanocarpa)

Abstract: The effects of aronia powder on the rheological and sensory characteristics of Sulgidduk were investigated. The moisture content of Sulgidduk ranged from 40.86 to 44.40%; however, addition of aronia powder to Sulgidduk tended to decrease its moisture content. With regard to the rheological properties, the addition of aronia powder decreased the hardness, springiness, adhesiveness, cohesiveness, chewiness, gumminess, and brittleness of Sulgidduk. Chromaticity determination revealed a decrease in L and b values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 23 publications
1
1
0
1
Order By: Relevance
“…It was reported that the total polyphenol content of rice cake without aronia powder was 4.55 mg GAE/g, but the total polyphenol content of rice cake without pistachio powder in this experiment was 40.00 μg GAE/g. Therefore, it was confirmed that there was about a 10-fold difference in the experimental results of this study (Hwang and Hwang, 2015). Another study confirmed the presence of total polyphenols in pistachios, and it was found that the phenol content was low when roasted (Abe et al, 2010).…”
Section: Analysis Of Total Phenol and Flavonoid Contents Insupporting
confidence: 78%
“…It was reported that the total polyphenol content of rice cake without aronia powder was 4.55 mg GAE/g, but the total polyphenol content of rice cake without pistachio powder in this experiment was 40.00 μg GAE/g. Therefore, it was confirmed that there was about a 10-fold difference in the experimental results of this study (Hwang and Hwang, 2015). Another study confirmed the presence of total polyphenols in pistachios, and it was found that the phenol content was low when roasted (Abe et al, 2010).…”
Section: Analysis Of Total Phenol and Flavonoid Contents Insupporting
confidence: 78%
“…As aronia cannot be harvested all year long and has a strong sour and astringent taste as compared to other berries, research is being conducted to add it to various processed Effects of different cultivated regions on bioactive compound content and antioxidant activity of aronia (Aronia melanocarpa) foods in the form of lyophilized powder or extract, instead of eating raw fruits (Hwang and Thi, 2014). Aronia cultivation is increasing, and research shows that ingestion of aronia is beneficial to health, adding aronia to various foods such as juice, yogurt, rice cakes, and cookies (Hwang and Hwang, 2015;Lee and Choi, 2016;Nguyen and Hwang, 2016). Although the development and demand for processed products containing aronia is increasing, few studies have been conducted to compare the antioxidant contents of aronia growing regions.…”
Section: Introductionmentioning
confidence: 99%
“…따라서 외국에서는 아로니아를 착즙 액이나 농축액으로 제조한 후에 다른 과실류와 혼합하여 주 스를 제조하거나, 천연색소 및 의약품의 원료로 이용하고 있 다 (Sidor 등, 2019;Tsuda, 2012). 국내에서도 아로니아를 첨 가한 설기떡, 스펀지케이크, 머핀, 쿠키, 잼 등 다양한 제품들 이 개발되고 있다(Hwang과 Hwang, 2015;Hwang과 Tai, 2014;Jang 등, 2018;Lee와 Choi, 2016;Park과 Chung, 2014 Aronia powder (3, 6 and 9%) was added based on the total weight of porridge. (Lee 등, 2005).…”
unclassified